Application of Renewable Energies for Storage of Horticultural Produce in Marginal areas of Kenya - Makanga, J.T; Shitanda, D; Njoroge, C; Ong'era, M.G (My University, 2017)
The objective of the research were to a prototype solar-charcoal cooler and test its performance in the temperature development and products storage ability. A prototype solar-charcoal cooler was developed at the Biomechanical and Environmental Engineering Department (BEED), College of Engineering and Technology of the Jomo Kenyatta University of Agriculture and Technology (JKUAT), Kenya and performance tested in terms of temperature and product storage ability. The performance of the cooler indicated positive results as regards to ideal parameters affecting produce storage. These parameters mainly included variations in temperature and humidity to levels ideal to product storage. The results also indicated that various fruits and vegetables including paw paws and spinach could be stored in the cooler for longer periods as compared to when they were under ambient conditions.
Keywords: Renewable; energies; Storage; Horticultutural; Produce; Solar-charcoal; Cooler